If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4 + x) = 3(3x + -1) + -9 (4 * 5 + x * 5) = 3(3x + -1) + -9 (20 + 5x) = 3(3x + -1) + -9 Reorder the terms: 20 + 5x = 3(-1 + 3x) + -9 20 + 5x = (-1 * 3 + 3x * 3) + -9 20 + 5x = (-3 + 9x) + -9 Reorder the terms: 20 + 5x = -3 + -9 + 9x Combine like terms: -3 + -9 = -12 20 + 5x = -12 + 9x Solving 20 + 5x = -12 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 20 + 5x + -9x = -12 + 9x + -9x Combine like terms: 5x + -9x = -4x 20 + -4x = -12 + 9x + -9x Combine like terms: 9x + -9x = 0 20 + -4x = -12 + 0 20 + -4x = -12 Add '-20' to each side of the equation. 20 + -20 + -4x = -12 + -20 Combine like terms: 20 + -20 = 0 0 + -4x = -12 + -20 -4x = -12 + -20 Combine like terms: -12 + -20 = -32 -4x = -32 Divide each side by '-4'. x = 8 Simplifying x = 8
| 3(5d+10)=45 | | 5xyz-42.24(83.3333xyz)=2 | | 87-x=7x+22 | | 4x+7=0 | | 6x^2-16x=49 | | 23x+d(56y)=59.78 | | x^3+3x^2+2x+1=0 | | 3x+28=12x-44 | | 10x-3=29+6x | | 3x+28=2x-44 | | c+4=d | | -0.3a+1.4=-1.2-0.7a | | 3x+4=4x-3 | | 6x+5=71 | | 5z+7-2z=32-2z | | 3+6x=-69 | | 5.7x+3=4.2x-3 | | (16-8)= | | 26(16-8)= | | x^2+16x-10=0 | | -7x-3=-45 | | 10b-2b= | | 9g-7g+5g= | | 1+6(2-1)= | | 99-5x=22x+15 | | 14-10x=54-24x | | 3x+2(x+2)=20(2x-5) | | 7-5x=5-7x | | -18x+50=0 | | 8x-3=9-2x | | 24x^2-2x-15=0 | | 6x^5-2x^4+6x^3-12x^5-6x^3-12x^5-6x^4+9x^3= |